Building better learners: exploring positive emotions and life satisfaction as keys to academic engagement - Wang, Xiaoling; Wan Jaafar, Wan Marzuki; Sulong, Rose Manisah (Frontiers in Education, 2025)
PurposeThis study investigates the relationships between positive emotions, life satisfaction, and academic engagement (absorption, vigor, and dedication) among undergraduates. Drawing on the broaden-and-build theory, the research aims to clarify how positive emotions influence academic engagement, both directly and indirectly, through enhanced life satisfaction.MethodsA total of 335 university students (197 female, 138 male) from four universities in southern Sichuan, China, participated in the research. Data were collected through three online self-report questionnaires measuring positive emotions, life satisfaction, and academic engagement.FindingsThe results demonstrate that positive emotions have significant direct effects on life satisfaction and academic engagement. Furthermore, life satisfaction mediated the relationship between positive emotions and academic engagement, highlighting crucial roles in enhancing student involvement.SignificanceExamine how positive emotions affect academic engagement in Chinese universities, underscoring the importance of cultivating positive atmosphere for both personal wellbeing and academic success. The findings also reinforce the Broaden and Build theory, showing that roles of positive emotions as essential resources for life satisfaction and academic development.